(untitled) (Journal of actual problems of jurisprudence, 2018)
The questions of interpretation of constitutional law at the present stage are analyzed in the article based on the examples of legislation and law enforcement practice of the Republic of Kazakhstan and foreign countries. Implementation issues of the Constitution, effectiveness of which largely depends on the correct and timely interpretation of its rules are studied. Key words: the Constitution, law interpretation, constitutional formation, official explanation, interpretation, constitutional security.